Threat Perception with COVID-19 Prevention Behavior in Community in Sukoharjo - Haryanti, Titik -; Azmiardi, Akhmad -; -, Ardyasih - (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2022)
Background: Currently, almost all countries in the world are experiencing cases of the COVID-19 pandemic. The COVID-19 disease has been declared as a pandemic by the World Health Organization (WHO) after almost most of the countries in the world were infected with COVID-19. One of the ways to prevent COVID-19 is determined by perception of threat to COVID-19 that occurs in the community. Objectives: This study aims to determine the relationship between threat perception and COVID-19 prevention behavior in Sukoharjo Regency. Methods: The type of research used was analytical observational with a cross-sectional approach. The population was all residents aged 15-65 years in Sukoharjo Regency of 618,992 in 2018 with a total sample of 246 people from simple random sampling technique. The research was conducted in October-December 2020. The research instrument used was questionnaires which were filled out directly by the respondents through google form. The research variables were threat perception and COVID-19 prevention behavior. Bivariate statistical test using chi square test. Results: The results showed that respondent's perception of the threat of COVID-19, the perception was high (67.1%) with high COVID-19 prevention behavior as well (58.8%). Threat perception influenced mask wearing behavior (OR= 2.68; P value<0.031), hand washing behavior (OR= 3.39; P value<0.001), and social distancing behavior (OR= 3.39; P value<0.001). There was a relationship between threat perception and COVID-19 prevention behavior in Sukoharjo Regency (P value<0.000). Conclusion: The study concluded that threat perception was related to COVID-19 prevention behavior, both the behavior of using masks, washing hands and social distancing. There is a need for regional government policies to maintain the behavior of preventing COVID-19 in order to reduce the number of COVID-19 cases in Indonesia